CHEKLANGAN MULTIMEDIA VOSITALARI BILAN OʻQITISHNI TASHKIL QILISH - Xursandov, H.F.; Ahtamqulov M.А.; Ilashova, L.N. (SCIENCE and SOCIETY, 2024)
The modern educational process cannot be imagined without multimedia technologies. Multimedia technologies enhance the educational experience through innovative ways to improve interactions between teachers, students and the curriculum, and to apply learning to а more dynamic, continuous and extra-curricular world. The article discusses the concept of multimedia technologies in the educational process.